Face of Justice: Biometrics, Facial Recognition, and the Ethics of Intelligent Surveillance - Santosh Kumar; Manish Bharadwaj (AG Volumes, 2026)
Artificial Intelligence (AI) has greatly improved biometric technologies, such as facial recognition, which are now an essential part of intelligent surveillance and contemporary criminal justice systems. It is a review of the principles, applications, opportunities, ethical considerations and regulatory issues on the use of AI powered Facial Recognition Technology in India. It outlines the basics of biometric modalities, how facial recognition works, and some of the ways it can be applied in law enforcement, border security, smart cities, and digital identity management. The review also emphasizes the efficiency and effectiveness of smart surveillance in crime prevention and suspect identification, as well as its limitations and the need for human monitoring. Ethical concerns such as privacy and data protection, algorithmic bias, civil liberties and new regulatory frameworks are critically analyzed, as are future policy trends and directions to support responsible and ethical use of biometric surveillance technology, to ensure that it is transparent, secure and accountable.